SYNTHESIS AND STUDY OF SOME NOVEL ?-ARYLAMINO-2-OXY-5-METHYLPROPIOPHENONES AS POLYETHYLENE STABILIZERS - Akchurina, Tanzilya Kh; Israfilova, Zubeyda; Sadeghian, Nastaran; Taslimi, Parham; Farzaliyev, Vagif Medjid; Sujayev, Afsun R.; Efendiyeva, Khuraman; Taslimi, Parham; Sadeghian, Nastaran (Institute of Catalysis and Inorganic Chemistry, 2024)
The number of ?-arylamino-2-oxy-5-methylpropiophenones has been synthesized by reacting of ?dimethylamino-2-oxy-5-methylpropiophenone hydrochloric acid salt with aniline derivatives in order to use these compounds as stabilizers for polyethylene. It was shown that the thermal stability of the compounds, depending on the nature of the substituent in the aniline fragment of the molecule was observed in a temperature range between 165 and 213°C. All studied compounds, introduced into polyethylene, increased its resistance to temperature effects. It was revealed that ?-arylamino-2-oxy-5-methylpropiophenones had a stabilizing effect due to the suppression of thermo-oxidative degradation of polyethylene. They multiplied the oxidation induction period of polyethylene and reduced the rate of oxidation. Among the compounds studied ?-phenoxybenzylamino-2-oxy-5-methylpropiophenone showed the highest stabilizing effect. All studied compounds had sufficient light-stabilizing activity, substantially due the presence in their molecules of a strong intramolecular hydrogen bond IHB (OH ... O = C) of the chelate type between the phenolic hydroxyl proton and the carbonyl oxygen of the acyl group. © 2024 Elsevier B.V., All rights reserved.
B?Zİ YENİ ?-ARİLAMİNO-2-OKSİ-5-METİLPROPİOFENONLARIN POLİETİLEN STABİLİZATORU KİMİ SİNTEZİ V? T?TBİQİ
Keywords: Degradation; Polyethylene; Stabilizer; Thermo-Oxidative; ?-Arylamino-2-Oxy-5-Methylpropiophenones